PENGARUH PROSES PEMBELAJARAN DAN PROGRAM KERJA PRAKTEK TERHADAP PENGEMBANGAN SOFT SKILLS MAHASISWA - Suharyanti, Chandra (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2015)
The objectives of this research are to investigate: (1) whether or not there is a significant effect of the learning process on the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009; (2) whether or not there is a significant effect of the practical work program (apprenticeship) on the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009; and (3) whether or not there is a simultaneous effect of the learning process and the practical work program (apprenticeship) on the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009.            This research used the descriptive quantitative research method. The population of the research was all of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009. The samples of the research were taken by using the total sampling technique, and consisted of all of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009. The data of the research were gathered through questionnaire. They were then statistically analyzed by using the multiple correlation and regression technique analysis.            The results of the research are as follows: (1) there is a significant effect of the learning process on the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009 as indicated by the value of rcount = 0.532 > that of rtable = 0.329; (2) there is a significant effect of the practical work program (apprenticeship) on the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009 as shown by the value of rcount = 0.527 > that of rtable = 0.329; and (3) there is a simultaneous effect of the learning process and the practical work program (apprenticeship) on the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009 as pointed out by the value of Fcount = 12. 529 > that of Ftable = 3.285 at the significance level of 5%. In addition, the results of the research also show that the multiple linear regression equation is ? = 38.300 + 0.199 X1 + 0.558 X2, meaning that the development of soft skills of the students of the Office Administration Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University, the class of 2009 will increase or decrease as much as 0. 199 if there is an increase or a decrease of one unit of the learning process and will increase or decrease as much as 0.558 if there is an increase or a decrease of one unit of the practical work program (apprenticeship). Each independent variable has a contribution to the dependent variable. The relative contribution of the learning process on the development of soft skills of the students is 50.60%, and that of the practical work program (apprenticeship) on the development of soft skills of the students is 49.40%. Furthermore, the effective contribution of the learning process on the development of soft skills of the students is 21.84%, and that of the practical work program (apprenticeship) on the development of soft skills of the students is 21.32%. Keywords:        learning process, practical work program (apprenticeship), development of soft skills.